Anti-wear gear oil for axle of electric automobile and preparation method of anti-wear gear oil
By using special anti-wear additives in electric vehicle axle gear oil, nano-alumina shell and three-dimensional envelope layer are formed, the existing gear oil has been solved, and the service life of the gear is significantly extended.
Patent Information
- Application Number
- CN202411730634.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing electric vehicle axle gear oil has shortcomings in its wear resistance, oxidation resistance and corrosion resistance, resulting in aggravation gear wear and shortening service life.
An electric vehicle axle anti-wear gear oil consisting of sulfide alkyl phenol calcium, ash-free phosphate, zinc dialkyl dithiophosphate, trithylene phosphate, anti-oxidant, anti-emulsifier, viscosity regulator and special anti-wear additive is used to improve the anti-wear, anti-oxidation and corrosion inhibition performance by forming a nano-alumina shell and a three-dimensional envelope layer on the carrier substrate.
It significantly improves the wear resistance, oxidation and corrosion inhibition properties of gear oil, reduces the wear degree of gear, extends its service life, and ensures the grade and quality of gear oil.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, and in particular to an anti-wear gear oil for an electric vehicle axle and a preparation method thereof. Background Art
[0002] Electric vehicles are vehicles that use electricity as a power source, use motors to drive wheels, and comply with various requirements of road traffic and safety regulations. They are new energy vehicles. They include pure electric vehicles (BEV), hybrid electric vehicles (HEV) and fuel cell electric vehicles (FCEV). Since electric vehicles have less impact on the environment than traditional vehicles, their development prospects are widely optimistic.
[0003] As an important part of electric vehicles, automobile axles are used to bear the load of the car and maintain the normal driving of the car on the road. Automobile axles (also known as axles) are connected to the frame (or load-bearing body) through suspension, and wheels are installed at both ends. Automobile axles and gears have a close relationship, and they work together to transmit power and realize the drive of the vehicle. Gears often need gear oil when they are used. Gear oil is an important lubricant made of petroleum lubricant base oil or synthetic lubricant, with extreme pressure anti-wear agent and oiliness agent added. Gear oil should not only have good anti-wear, anti-foaming, shear stability, load resistance and suitable viscosity, but also have good thermal oxidation stability and anti-rust performance. The patent document with patent application number "CN202010858602.6" discloses a gear oil with an ultra-long oil change cycle and a preparation method thereof. The gear oil is made from the following raw materials: ultra-high viscosity olefin synthetic oil, polymethacrylate pour point depressant, viscosity index improver, pentaerythritol ester, long-acting compound, alkyl naphthalene base oil, defoamer, rust inhibitor, oiliness agent, detergent, extreme pressure anti-wear agent and metal deactivator.
[0004] Although the gear oil prepared in the above patent document has excellent low temperature resistance, its own anti-wear performance is relatively poor, which will aggravate the wear of the axle gear and shorten its service life. In addition, its antioxidant and corrosion resistance are relatively insufficient, and it is easy to produce sludge and sediment during use, which affects the lubrication effect and shortens the service life of the axle gear. Therefore, the present invention provides an anti-wear gear oil for electric vehicle axles and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide an anti-wear gear oil for an electric vehicle axle and a preparation method thereof. The anti-wear additive prepared by the present invention is used as a raw material for the gear oil, so that the gear oil has excellent anti-wear performance and also has excellent antioxidant and corrosion inhibition properties, effectively reducing the degree of wear of the gears and extending their service life, while also ensuring the grade and quality of the gear oil.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An anti-wear gear oil for an electric vehicle axle is composed of the following raw materials in parts by weight: 90-100 parts of base oil, 1.5-2.5 parts of sulfurized alkyl phenol calcium, 5-7 parts of ashless phosphate, 1.5-2.0 parts of dialkyl zinc dithiophosphate, 2-3 parts of tricresyl phosphate, 0.5-0.8 parts of dimethyl silicone oil, 0.6-1.0 parts of dodecenyl succinate, 2-3 parts of antioxidant, 1.2-1.8 parts of anti-emulsifier, 10-15 parts of viscosity modifier and 4-6 parts of anti-wear aid.
[0008] Furthermore, the preparation method of the anti-wear additive is as follows: the pretreated carrier substrate is uniformly dispersed in a composite solvent mixed with equal volumes of ethanol and toluene at a dosage ratio of 5 to 15 g / L, 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added in an amount of 0.4 to 0.6 times the mass of the pretreated carrier substrate and 0.3 to 0.5 times the mass of the polyaspartic acid are added under nitrogen protection, and benzoyl peroxide and benzotriazole are added in an amount of 0.2 to 0.4 times the mass of the pretreated carrier substrate and 0.5 to 0.8 times the mass of the polyaspartic acid are added in sequence after ultrasonic dispersion, and the temperature is raised to 80 to 90° C. after mixing, and the reaction is kept warm for 100 to 150 minutes under nitrogen protection, and then kept warm for 50 to 90 minutes at a temperature of 110 to 120° C.; after the reaction is completed, the reaction products are separated into solid and liquid in turn, and the obtained filter cakes are washed with toluene and 1,4-butylene oxide for 3 to 4 times respectively and then vacuum dried to obtain the anti-wear additive.
[0009] Furthermore, the preparation method of the pretreated carrier substrate is: add 3-isocyanatepropyltrimethoxysilane with a mass 1 to 2 times that of the carrier substrate to an acetone dispersion of the carrier substrate with a concentration of 0.02 to 0.05 g / mL, disperse evenly and reflux for 2 to 3 hours; after the reaction is completed, centrifuge, wash and vacuum dry the resulting components in sequence to obtain the pretreated carrier substrate.
[0010] Furthermore, the preparation method of the carrier substrate is:
[0011] Step 1, slowly drop an aqueous solution of ammonium aluminum sulfate with a mass of 0.5 to 0.6 times and a concentration of 0.6 to 1.0 g / mL into an aqueous solution of sodium hydroxide with a concentration of 10 to 15 wt% and a temperature of 80 to 85° C. at a stirring rate of 1000 to 1500 r / min, add an acid solution after standing for 2 to 3 hours, add a dispersion of molybdenum sulfide nanospheres with a mass of 0.8 to 0.9 times that of the aqueous solution of sodium hydroxide after the obtained mixed components form a colloid, continue stirring at a rate of 500 to 800 r / min for 30 to 50 minutes, then transfer it to a reaction device, evacuate and fill with nitrogen to drive out the air in the device, and then keep the reaction at a temperature of 150 to 180° C. for 8 to 15 hours; wherein the acid solution is a 25 to 35 wt% hydrochloric acid solution, and the molar ratio of hydrochloric acid to ammonium aluminum sulfate in the mixed components is 0.2 to 0.25:1;
[0012] Step 2: After the reaction is completed, cool naturally to room temperature, then add 2-3% by mass of a 10-15% aqueous solution of polyvinyl pyrrolidone to the resulting component, stir for 20-30 minutes and then filter, wash the resulting filter cake with anhydrous ethanol 3-4 times, and then perform solid-liquid separation and vacuum drying in sequence to obtain a carrier substrate.
[0013] Furthermore, the preparation method of the molybdenum sulfide nanosphere dispersion is as follows: molybdenum sulfide nanospheres are added into deionized water at a dosage ratio of 0.02 to 0.05 g / mL, and polyoxyethylene ether is added thereto at a mass ratio of 0.8 to 1.5% of deionized water, and the molybdenum sulfide nanosphere dispersion is obtained after ultrasonic dispersion for 30 to 40 minutes.
[0014] The preparation method of molybdenum sulfide nano-microspheres is as follows: ammonium molybdate is added into an ethanol aqueous solution with a volume concentration of 10-15% to prepare an ammonium molybdate solution with a Mo (VI) concentration of 0.02-0.05 mol / L, and then thioacetamide and polyvinyl pyrrolidone are respectively added to the ammonium molybdate solution, and hydrazine hydrate is added after stirring evenly, and the obtained mixed solution is kept warm at a temperature of 150-200°C for 1-2 days after being fully dispersed; after the reaction is completed, the resultant components are naturally cooled to room temperature, the precipitate is filtered out and washed with deionized water and anhydrous ethanol for 3-4 times respectively, and then transferred to a vacuum drying device, and vacuum dried at a temperature of 60-70°C for 8-10 hours, and the final obtained is the molybdenum sulfide nano-microspheres; wherein the molar ratio of sulfur ions to molybdenum ions in the mixed solution is 3-4:1; and the molar ratio of thioacetamide, hydrazine hydrate and polyvinyl pyrrolidone is 1-1.2:1:0.3-0.5.
[0015] Furthermore, the base oil is compounded by Shell X420 synthetic base oil and Mobil PAO4 polyalphaolefin base oil in a mass ratio of 4 to 6:1.
[0016] Furthermore, the antioxidant is prepared by compounding diphenyl isodecyl phosphite and 4,4'-dioctyl diphenylamine in a mass ratio of 1:1.5-2.
[0017] Furthermore, the demulsifier is selected from any one of demulsifier D114 and demulsifier T1001.
[0018] Furthermore, the viscosity modifier is selected from any one of Afton HiTEC 5777 and Afton HiTEC3339.
[0019] A method for preparing an anti-wear gear oil for an electric vehicle axle comprises the following steps: weighing various raw materials according to the formula amount and putting the base oil into a reaction kettle, adjusting the kettle temperature to 65-75°C, and stirring at this temperature for 30-40 minutes, then putting the remaining raw materials into the reaction kettle, and continuing to stir at this temperature for 2-3 hours, and the mixture obtained in the reaction kettle is the anti-wear gear oil for the electric vehicle axle.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention first adds an aqueous solution of ammonium aluminum sulfate into an aqueous solution of sodium hydroxide and then adds an acid solution, and when a colloid is generated, adds a dispersion of molybdenum sulfide nano-microspheres, and then forms a relatively dense nano-alumina shell layer on the surface of the molybdenum sulfide nano-microspheres through a heat preservation reaction, that is, the prepared carrier substrate is a spherical core-shell structure with the molybdenum sulfide nano-microspheres as the "core" and the nano-alumina as the "shell" layer. Then, the carrier substrate is pretreated with 3-isocyanatepropyltrimethoxysilane to obtain a pretreated carrier substrate, the pretreated carrier substrate is uniformly dispersed in a compound solvent, 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added thereto under the protection of nitrogen, and ultrasonic dispersion is performed so that the two are effectively dispersed and adsorbed on the surface of the nano-alumina shell layer, and then under the action of benzoyl peroxide, benzotriazole is effectively grafted on the surface of the pretreated carrier substrate with 3-isocyanatepropyltrimethoxysilane as a bridge, and finally a dense three-dimensional envelope layer is formed on its surface, thereby effectively "locking" the 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid adsorbed on the surface of the nano-alumina shell layer on the surface of the carrier substrate, reducing the probability of migration of the two, and finally preparing an anti-wear additive.
[0022] Since the carrier substrate is made of molybdenum sulfide and nano-alumina as raw materials, it has excellent anti-wear properties. Moreover, the spherical structure enables it to produce a bearing / ball effect when in use, which can convert sliding friction into partial rolling friction, playing a role similar to a "ball", effectively reducing its friction coefficient, and further improving the anti-wear properties of the carrier substrate. In addition, the presence of 2,6-di-tert-butyl-4-methylphenol can improve the antioxidant properties of the anti-wear aid to a certain extent, and the mutual synergy and cooperation between benzotriazole and polyaspartic acid make the anti-wear aid also have an excellent corrosion inhibition effect, which can slow down the rate of rusting of gears to a certain extent and extend their service life. In summary, the anti-wear aid prepared by the present invention is used as a raw material for gear oil, so that the gear oil has excellent anti-wear properties and also has excellent antioxidant and corrosion inhibition properties, effectively reducing the degree of wear of the gear, extending its service life, and also ensuring the grade and quality of the gear oil. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] An anti-wear gear oil for an electric vehicle axle, comprising the following raw materials in parts by weight: 90 parts of base oil, 1.5 parts of sulfurized alkyl phenol calcium, 5 parts of ashless phosphate, 1.5 parts of dialkyl zinc dithiophosphate, 2 parts of tricresyl phosphate, 0.5 parts of dimethyl silicone oil, 0.6 parts of dodecenyl succinate, 2 parts of antioxidant, 1.2 parts of anti-emulsifier D114, 10 parts of viscosity modifier Afton HiTEC 5777 and 4 parts of anti-wear additive;
[0026] The base oil is compounded by Shell X420 synthetic base oil and Mobil PAO4 polyalphaolefin base oil in a mass ratio of 4:1; the antioxidant is compounded by diphenyl isodecyl phosphite and 4,4'-dioctyl diphenylamine in a mass ratio of 1:1.5.
[0027] The preparation method of the anti-wear additive is as follows: the pre-treated carrier substrate is uniformly dispersed in a composite solvent mixed with equal volumes of ethanol and toluene at a dosage ratio of 5g / L, and 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added in an amount of 0.4 times the mass of the pre-treated carrier substrate and 0.3 times the mass of the pre-treated carrier substrate respectively under nitrogen protection, and benzoyl peroxide and benzotriazole are added in an amount of 0.2 times the mass of the pre-treated carrier substrate and 0.5 times the mass of the pre-treated carrier substrate respectively after ultrasonic dispersion, and the temperature is raised to 80°C after mixing, and the reaction is kept warm for 100 minutes under nitrogen protection, and then kept warm for 50 minutes at 110°C; after the reaction is completed, the reaction products are separated into solid and liquid in turn, and the obtained filter cakes are washed with toluene and 1,4-butylene oxide for 3 times respectively and then vacuum dried to obtain the anti-wear additive.
[0028] The preparation method of the pretreated carrier substrate is as follows: add 3-isocyanatepropyltrimethoxysilane in an amount equal to the mass of the carrier substrate to an acetone dispersion of the carrier substrate with a concentration of 0.02 g / mL, disperse the dispersion uniformly, and reflux for reaction for 2 hours; after the reaction is completed, centrifuge, wash, and vacuum dry the resulting components in sequence to obtain the pretreated carrier substrate.
[0029] The preparation method of the carrier substrate is:
[0030] Step 1, slowly drop an aqueous solution of ammonium aluminum sulfate with a mass of 0.5 times and a concentration of 0.6 g / mL into an aqueous solution of sodium hydroxide with a concentration of 10wt% and a temperature of 80°C at a stirring rate of 1000r / min, add an acid solution after standing for 2h, add a dispersion of molybdenum sulfide nanospheres with a mass of 0.8 times that of the aqueous solution of sodium hydroxide after the obtained mixed components form a colloid, continue stirring at a rate of 500r / min for 30min, then transfer it to a reaction device, evacuate and fill with nitrogen to drive out the air in the device, and then keep the reaction at a temperature of 150°C for 8h; wherein the acid solution is a 25wt% hydrochloric acid solution, and the molar ratio of hydrochloric acid to ammonium aluminum sulfate in the mixed components is 0.2:1;
[0031] The preparation method of the molybdenum sulfide nanosphere dispersion is as follows: adding the molybdenum sulfide nanospheres into deionized water at a dosage ratio of 0.02 g / mL, adding polyoxyethylene ether in an amount of 0.8% of the deionized water, and ultrasonically dispersing for 30 minutes to obtain the molybdenum sulfide nanosphere dispersion;
[0032] The preparation method of molybdenum sulfide nano-microspheres is as follows: ammonium molybdate is added into an ethanol aqueous solution with a volume concentration of 10% to prepare an ammonium molybdate solution with a Mo (VI) concentration of 0.02 mol / L, and then thioacetamide and polyvinyl pyrrolidone are respectively added to the ammonium molybdate solution, and hydrazine hydrate is added after stirring evenly, and the obtained mixed solution is kept at a temperature of 150°C for 1 day after being fully dispersed; after the reaction is completed, the resultant components are naturally cooled to room temperature, the precipitate is filtered out and washed with deionized water and anhydrous ethanol for 3 times respectively, and then transferred to a vacuum drying equipment, and vacuum dried at a temperature of 60°C for 8 hours, and the final obtained is molybdenum sulfide nano-microspheres; wherein the molar ratio of sulfur ions to molybdenum ions in the mixed solution is 3:1; and the molar ratio of thioacetamide, hydrazine hydrate and polyvinyl pyrrolidone is 1:1:0.3;
[0033] Step 2: After the reaction is completed, cool naturally to room temperature, then add 2% by mass of a 10% aqueous solution of polyvinyl pyrrolidone to the resulting component, stir for 20 minutes and then filter, wash the filter cake with anhydrous ethanol three times, and then perform solid-liquid separation and vacuum drying in sequence to obtain a carrier substrate.
[0034] A method for preparing an anti-wear gear oil for an electric vehicle axle comprises the following steps: weighing various raw materials according to the formula amount and putting the base oil into a reactor, adjusting the reactor temperature to 65°C, and stirring at this temperature for 30 minutes, then putting the remaining raw materials into the reactor, and continuing to stir at this temperature for 2 hours, and the mixture obtained in the reactor is the anti-wear gear oil for the electric vehicle axle.
[0035] Example 2
[0036] The production method of an anti-wear gear oil for an electric vehicle axle provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used and the preparation method of the anti-wear additive used in the two are not exactly the same, and the specific composition of the raw materials used in this embodiment and the preparation method of the anti-wear additive are as follows:
[0037] An anti-wear gear oil for an electric vehicle axle, comprising the following raw materials in parts by weight: 95 parts of base oil, 2 parts of sulfurized alkyl phenol calcium, 6 parts of ashless phosphate, 1.5 parts of dialkyl zinc dithiophosphate, 2.5 parts of tricresyl phosphate, 0.6 parts of dimethyl silicone oil, 0.8 parts of dodecenyl succinate, 2.5 parts of antioxidant, 1.5 parts of anti-emulsifier T1001, 12 parts of viscosity modifier Afton HiTEC3339 and 5 parts of anti-wear additive;
[0038] The base oil is compounded by Shell X420 synthetic base oil and Mobil PAO4 polyalphaolefin base oil in a mass ratio of 5:1; the antioxidant is compounded by diphenyl isodecyl phosphite and 4,4'-dioctyl diphenylamine in a mass ratio of 1:2.
[0039] The preparation method of the anti-wear additive is as follows: the pre-treated carrier substrate is uniformly dispersed in a composite solvent mixed with equal volumes of ethanol and toluene at a dosage ratio of 10 g / L, and 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added in an amount of 0.5 times the mass of the pre-treated carrier substrate and 0.4 times the mass of the pre-treated carrier substrate respectively under nitrogen protection, and benzoyl peroxide and benzotriazole are added in an amount of 0.3 times the mass of the pre-treated carrier substrate and 0.6 times the mass of the pre-treated carrier substrate respectively after ultrasonic dispersion, and the temperature is raised to 85°C after mixing, and the reaction is kept warm for 120 minutes under nitrogen protection, and then kept warm for 70 minutes at 110°C; after the reaction is completed, the reaction products are separated into solid and liquid in turn, and the obtained filter cakes are washed with toluene and 1,4-butylene oxide for 3 times respectively and then vacuum dried to obtain the anti-wear additive.
[0040] The preparation method of the pretreated carrier substrate is as follows: add 3-isocyanatepropyltrimethoxysilane in an amount 1.5 times the mass of the carrier substrate to an acetone dispersion of the carrier substrate with a concentration of 0.03 g / mL, disperse uniformly and reflux for reaction for 3 hours; after the reaction is completed, centrifuge, wash and vacuum dry the resulting components in sequence to obtain the pretreated carrier substrate.
[0041] The preparation method of the carrier substrate is:
[0042] Step 1, slowly drop an aqueous solution of ammonium aluminum sulfate with a mass of 0.6 times and a concentration of 0.8 g / mL into an aqueous solution of sodium hydroxide with a concentration of 10wt% and a temperature of 80°C at a stirring rate of 1200r / min, add an acid solution after standing for 3 hours, add a dispersion of molybdenum sulfide nanospheres with a mass of 0.85 times that of the aqueous solution of sodium hydroxide after the obtained mixed components form a colloid, continue stirring at a rate of 600r / min for 40 minutes, then transfer it to a reaction device, evacuate and fill with nitrogen to drive out the air in the device, and then keep the reaction at a temperature of 160°C for 10 hours; wherein the acid solution is a 30wt% hydrochloric acid solution, and the molar ratio of hydrochloric acid to ammonium aluminum sulfate in the mixed components is 0.25:1;
[0043] The preparation method of the molybdenum sulfide nanosphere dispersion is as follows: adding the molybdenum sulfide nanospheres into deionized water at a dosage ratio of 0.02 g / mL, adding polyoxyethylene ether in an amount of 1.2% of the deionized water, and ultrasonically dispersing for 30 minutes to obtain the molybdenum sulfide nanosphere dispersion;
[0044] Step 2: After the reaction is completed, cool naturally to room temperature, then add 3% by mass of a 15% aqueous solution of polyvinyl pyrrolidone to the resulting component, stir for 25 minutes and filter, wash the resulting filter cake three times with anhydrous ethanol, and then perform solid-liquid separation and vacuum drying in sequence to obtain a carrier substrate.
[0045] Example 3
[0046] The production method of an anti-wear gear oil for an electric vehicle axle provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used and the preparation method of the anti-wear additive used in the two are not exactly the same, and the specific composition of the raw materials used in this embodiment and the preparation method of the anti-wear additive are as follows:
[0047] An anti-wear gear oil for an electric vehicle axle is composed of the following raw materials in parts by weight: 100 parts of base oil, 2.5 parts of sulfurized alkyl phenol calcium, 7 parts of ashless phosphate, 2 parts of dialkyl zinc dithiophosphate, 3 parts of tricresyl phosphate, 0.8 parts of dimethyl silicone oil, 1 part of dodecenyl succinate, 3 parts of antioxidant, 1.8 parts of anti-emulsifier D114, 15 parts of viscosity modifier Afton HiTEC5777 and 6 parts of anti-wear additive.
[0048] The base oil is compounded by Shell X420 synthetic base oil and Mobil PAO4 polyalphaolefin base oil in a mass ratio of 6:1; the antioxidant is compounded by diphenyl isodecyl phosphite and 4,4'-dioctyl diphenylamine in a mass ratio of 1:2.
[0049] The preparation method of the anti-wear additive is as follows: the pre-treated carrier substrate is uniformly dispersed in a compound solvent mixed with equal volumes of ethanol and toluene at a dosage ratio of 15g / L, and 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added in an amount of 0.6 times the mass of the pre-treated carrier substrate and 0.5 times the mass of the polyaspartic acid under nitrogen protection, and benzoyl peroxide and benzotriazole are added in an amount of 0.4 times the mass of the pre-treated carrier substrate and 0.8 times the mass of the pre-treated carrier substrate respectively after ultrasonic dispersion, and the temperature is raised to 90°C after mixing, and the reaction is kept warm for 150 minutes under nitrogen protection, and then kept warm for 90 minutes at 120°C; after the reaction is completed, the reaction products are separated into solid and liquid in turn, and the obtained filter cakes are washed with toluene and 1,4-butylene oxide 4 times respectively and then vacuum dried to obtain the anti-wear additive.
[0050] The preparation method of the pretreated carrier substrate is as follows: add 3-isocyanatepropyltrimethoxysilane in an amount twice the mass of the carrier substrate to an acetone dispersion of the carrier substrate with a concentration of 0.05 g / mL, disperse uniformly and reflux for reaction for 3 hours; after the reaction is completed, centrifuge, wash and vacuum dry the resulting components in sequence to obtain the pretreated carrier substrate.
[0051] The preparation method of the carrier substrate is:
[0052] Step 1, slowly drop an aqueous solution of ammonium aluminum sulfate with a mass of 0.6 times and a concentration of 1.0 g / mL into an aqueous solution of sodium hydroxide with a concentration of 15wt% and a temperature of 85°C at a stirring rate of 1500r / min, add an acid solution after standing for 3 hours, add a dispersion of molybdenum sulfide nanospheres with a mass of 0.9 times that of the aqueous solution of sodium hydroxide after the obtained mixed components form a colloid, continue stirring at a rate of 800r / min for 50 minutes, then transfer it to a reaction device, evacuate and fill with nitrogen to drive out the air in the device, and then keep the reaction at a temperature of 180°C for 15 hours; wherein the acid solution is a 35wt% hydrochloric acid solution, and the molar ratio of hydrochloric acid to ammonium aluminum sulfate in the mixed components is 0.25:1;
[0053] The preparation method of the molybdenum sulfide nanosphere dispersion is as follows: adding the molybdenum sulfide nanospheres into deionized water at a dosage ratio of 0.05 g / mL, adding polyoxyethylene ether in an amount of 1.5% of the deionized water, and ultrasonically dispersing for 40 minutes to obtain the molybdenum sulfide nanosphere dispersion;
[0054] Step 2: After the reaction is completed, cool naturally to room temperature, then add 3% by mass of a 15% aqueous solution of polyvinyl pyrrolidone to the resulting component, stir for 30 minutes and filter, wash the resulting filter cake with anhydrous ethanol 4 times, and then perform solid-liquid separation and vacuum drying in sequence to obtain a carrier substrate.
[0055] Comparative Example 1: The main difference between this comparative example and Example 1 is that an equal amount of molybdenum sulfide nano-microspheres are used to replace the anti-wear additive in this comparative example.
[0056] Comparative Example 2: The main difference between this comparative example and Example 1 is that in this comparative example, an equal amount of carrier substrate is used to replace the anti-wear additive.
[0057] Comparative Example 3: The main difference between this comparative example and Example 1 is that in this comparative example, 2,6-di-tert-butyl-4-methylphenol is not used in the process of preparing the anti-wear additive.
[0058] Comparative Example 4: The main difference between this comparative example and Example 1 is that polyaspartic acid is not used in the process of preparing the anti-wear additive in this comparative example.
[0059] Performance Testing
[0060] The relevant physical and chemical indicators of the gear oil samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested respectively, and the obtained test data were recorded in the following table:
[0061] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Test methods Copper corrosion (121℃, 3h) / level 1a 1a 1a 1a 1a 1a 1a GB / T5096 Liquid phase corrosion (artificial seawater) Rust-free Rust-free Rust-free Medium Rust Medium Rust Light Rust Light Rust GB / T11143 Oxidation performance (121℃, 312h) 100℃ kinematic viscosity increase / % precipitation value / mL 1.160.00 1.070.00 1.120.00 2.830.06 2.650.05 1.430.02 1.380.02 SH / T0123 Friction coefficient (MTM) Friction coefficient (40℃) 0.028 0.027 0.027 0.030 0.027 0.027 0.028 MTM Micro-traction Tester <![CDATA[Sintering load in the four-ball machine test (P D ) / N Wear scar diameter (196 N, 60 min, 54 °C, 1800 r / min) / mm]]> 62830.26 63380.25 63160.25 58650.29 63020.26 62540.27 62670.26 GB / T 3142SH / T0189
[0062] Note: Medium rust in the liquid phase rust grade means moderate rust, light rust means slight rust, and no rust means no rust; the specific classification is as follows:
[0063] 1. Moderate rust: There are multiple small areas of rust, and the local finish is slightly affected.
[0064] 2. Slight rust: There is a very small amount of rust on the surface, usually only in a small area, but the overall smoothness is basically maintained.
[0065] 3. No rust: There is absolutely no sign of rust on the surface.
[0066] By comparing and analyzing the relevant data in the table, it can be seen that the anti-wear additive prepared by the present invention is used as a raw material for gear oil, so that the gear oil has excellent anti-wear performance and also has excellent antioxidant and corrosion inhibition performance, effectively reducing the wear degree of the gear and extending its service life, while also ensuring the grade and quality of the gear oil. This shows that the anti-wear gear oil for electric vehicle axles and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0067] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An anti-wear gear oil for an electric vehicle axle, characterized in that: The invention is composed of the following raw materials in parts by weight: 90 to 100 parts of base oil, 1.5 to 2.5 parts of alkyl phenol calcium sulfide, 5 to 7 parts of ashless phosphate, 1.5 to 2.0 parts of dialkyl zinc dithiophosphate, 2 to 3 parts of tricresyl phosphate, 0.5 to 0.8 parts of dimethyl silicone oil, 0.6 to 1.0 parts of dodecenyl succinate, 2 to 3 parts of antioxidant, 1.2 to 1.8 parts of anti-emulsifier, 10 to 15 parts of viscosity modifier and 4 to 6 parts of anti-wear aid.
2. The anti-wear gear oil for electric vehicle axles according to claim 1, characterized in that: The preparation method of the anti-wear additive is as follows: a pre-treated carrier substrate is uniformly dispersed in a composite solvent mixed with equal volumes of ethanol and toluene at a dosage ratio of 5-15 g / L, 2,6-di-tert-butyl-4-methylphenol and polyaspartic acid are added in an amount of 0.4-0.6 times the mass of the pre-treated carrier substrate and 0.3-0.5 times the mass of the polyaspartic acid are added under nitrogen protection, benzoyl peroxide and benzotriazole are added in an amount of 0.2-0.4 times the mass of the pre-treated carrier substrate and 0.5-0.8 times the mass of the polyaspartic acid are added in sequence after ultrasonic dispersion, the mixture is uniformly mixed, the temperature is raised to 80-90° C., the mixture is kept warm for reaction for 100-150 minutes under nitrogen protection, and then kept warm for reaction at a temperature of 110-120° C. for reaction for 50-90 minutes; after the reaction is completed, the reaction products are separated into solid and liquid in sequence, the obtained filter cakes are washed with toluene and 1,4-butylene oxide for 3-4 times respectively, and then vacuum dried, and the obtained anti-wear additive is obtained.
3. The anti-wear gear oil for an electric vehicle axle according to claim 2, characterized in that: The preparation method of the pretreated carrier substrate comprises: adding 3-isocyanatepropyltrimethoxysilane in an amount 1 to 2 times the mass of the carrier substrate to a carrier substrate acetone dispersion having a concentration of 0.02 to 0.05 g / mL, uniformly dispersing the mixture and subjecting the mixture to reflux reaction for 2 to 3 hours; after the reaction is completed, centrifuging, washing and vacuum drying the obtained product components in sequence to obtain the pretreated carrier substrate.
4. The anti-wear gear oil for electric vehicle axles according to claim 3, characterized in that: The preparation method of the carrier substrate is: Step 1, slowly drop an aqueous solution of ammonium aluminum sulfate with a mass of 0.5 to 0.6 times and a concentration of 0.6 to 1.0 g / mL into an aqueous solution of sodium hydroxide with a concentration of 10 to 15 wt% and a temperature of 80 to 85° C. at a stirring rate of 1000 to 1500 r / min, add an acid solution after standing for 2 to 3 hours, add a dispersion of molybdenum sulfide nanospheres with a mass of 0.8 to 0.9 times that of the aqueous solution of sodium hydroxide after the obtained mixed components form a colloid, continue stirring at a rate of 500 to 800 r / min for 30 to 50 minutes, then transfer it to a reaction device, evacuate and fill with nitrogen to drive out the air in the device, and then keep the reaction at a temperature of 150 to 180° C. for 8 to 15 hours; wherein the acid solution is a 25 to 35 wt% hydrochloric acid solution, and the molar ratio of hydrochloric acid to ammonium aluminum sulfate in the mixed components is 0.2 to 0.25:1; Step 2: After the reaction is completed, cool naturally to room temperature, then add 2-3% by mass of a 10-15% aqueous solution of polyvinyl pyrrolidone to the resulting component, stir for 20-30 minutes and then filter, wash the resulting filter cake with anhydrous ethanol 3-4 times, and then perform solid-liquid separation and vacuum drying in sequence to obtain a carrier substrate.
5. The anti-wear gear oil for an electric vehicle axle according to claim 4, characterized in that: The preparation method of the molybdenum sulfide nanosphere dispersion is as follows: adding molybdenum sulfide nanospheres into deionized water at a dosage ratio of 0.02 to 0.05 g / mL, adding polyoxyethylene ether in an amount of 0.8 to 1.5% of the deionized water, and ultrasonically dispersing for 30 to 40 minutes to obtain the molybdenum sulfide nanosphere dispersion.
6. The anti-wear gear oil for electric vehicle axles according to claim 1, characterized in that: The base oil is compounded by mixing Shell X420 synthetic base oil and Mobil PAO4 polyalphaolefin base oil in a mass ratio of 4 to 6:
1.
7. The anti-wear gear oil for an electric vehicle axle according to claim 1, characterized in that: The antioxidant is prepared by compounding diphenyl isodecyl phosphite and 4,4'-dioctyl diphenylamine in a mass ratio of 1:1.5-2.
8. The anti-wear gear oil for an electric vehicle axle according to claim 1, characterized in that: The demulsifier is selected from any one of demulsifier D114 and demulsifier T1001.
9. The anti-wear gear oil for an electric vehicle axle according to claim 1, characterized in that: The viscosity modifier is selected from any one of Afton HiTEC 5777 and Afton HiTEC3339.
10. A method for preparing the anti-wear gear oil for an electric vehicle axle according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: weighing various raw materials according to the formula amount and putting the base oil into a reaction kettle, adjusting the kettle temperature to 65-75°C, and stirring at this temperature for 30-40 minutes, then putting the remaining raw materials into the reaction kettle, and continuing to stir at this temperature for 2-3 hours, and the mixture obtained in the reaction kettle is the anti-wear gear oil for electric vehicle axles.
Citation Information
Patent Citations
Gear oil with ultra-long oil change period and preparation method thereof
CN112126494A
Preparation method of embedded solid lubricant
CN110257129A
Cutting oil for metal processing and preparation method thereof
CN115058273A
A kick board Detachable Rail Bike
KR1020250010483A
Powder transfer device
KR1020250015371A